Hepatothorax: A Rare Outcome of High-Speed Trauma. (24th November 2011) - Porcelli, Matthew; Prychyna, Oksana; Rosenthal, Andrew; DeCostanza, Joseph
Abstract : Diaphragmatic ruptures are the result of severe blunt trauma or penetrating trauma. Motor vehicle crashes are a common mechanism associated with blunt diaphragmatic rupture (BDR). Incorporating diagnostic tools and laparotomy assist in the diagnosis and treatment of BDR. However, diagnosing BDR can be a challenge for practitioners. Early diagnosis and treatment improve the patient's outcomes. This paper details the events of a patient received in a level I trauma unit.